Warrant of Termination of Investigation (SP3) Issued Based on Peace Agreement Between Suspects and Reporters in Ordinary Offences - Hakiki, Azizul (University of Jember, 2019)
Warrant of Termination of Investigation (SP3 – Surat Perintah Penghentian Penyidikan) is applied as the power granted to the investigator of a criminal act. Article 109 paragraph (2) of Law No. 8 of 1981 on the Criminal Procedure Code (KUHAP – Kitab Undang-Undang Hukum Acara Pidana) states that there are three requirements to stop a criminal investigation: (a) insufficient evidence; (b) the act committed by the suspect is not a criminal offence; and (c) the investigation is stopped by law. These three conditions are alternative conditions. At the implementation level, there are many cases that are terminated because they fulfill these three requirements. However, it is not uncommon for cases that have progressed to the stage of investigation be stopped as well because the suspected and the reporter reached a peace agreement through mediation facilitated by police investigators. The mediation condition will impact the ongoing investigation since the investigation should be stopped and police should revoke the report of the investigation concerned. Whereas, in this context, the status of this case is an ordinary offence status which means that the revocation of the report has no consequences with the ongoing investigation. Peace agreements impact ongoing investigations. Whereas the investigation should be stopped and police should revoke the offense report, under extant legislation, investigations maintain ordinary offence status, meaning revocation of the offense report has no effect on the ongoing investigation. The investigation cannot be stopped with any other reasons excepts those that stated in Article 109 paragraph (2). The fact that the revocation of the report of investigation leads to the termination of the ongoing investigation as evidenced by the issuance of SP3. While the issuance of SP3 enables termination of an ongoing investigation by revoking the report of investigation, investigation termination requirements explicitly state that an agreement reached through a mediation mechanism cannot provide legal grounds to issue SP3. This paper provides a normative legal analysis of the validity of investigation termination as the result of an agreement reached through a mediation mechanism. Investigations that terminated based on an agreement achieved by mediation mechanism will create space for third parties to utilize a pre-trial mechanism whose purpose is to test the validity or termination of the investigation. Keywords: Termination of Investigation, Criminal Law, Criminal Procedure.